Custody hearing. Legal basis - Bazán Cerdán, J. Fernando (2010)
This article analyzes the legal grounds (legal nature, general aspects and scope) of the protection of rights, a very new institution within the criminal procedural scope, introduced by article 71, subsection 4 of the Criminal Procedure Code of 2004. Finally, it concludes by questioning the specific nature of the legally protected rights according to a systematic interpretation of the provision that regulates it.